A roadmap for comparing readmission policies with application to Denmark, England, Germany and the United States. Issue 3 (March 2015) - Kristensen, Søren Rud; Bech, Mickael; Quentin, Wilm
Highlights Hospital readmissions receive increasing interest from policy makers. Reducing readmissions has potential to simultaneously improve quality and save cost. The aims of readmission policies vary across countries. The presented framework provides a road map for policy makers' assessment of policy.